An Approach to Measuring Potential Upgrading Demand in the Housing Market - Winger, Alan R. (The Review of Economics and Statistics, 1963)
T HIS paper is concerned with the problem of measuring potential upgrading demand in the housing market. We seek to develop a means of identifying in sample survey data families who might make a housing adjustment that would provide them with more housing space or higher cost housing. Our analytical framework is a form of cross section demand analysis, with the focus on housing stocks of individual families. We assume these stocks are held because of the services they provide and that each family chooses to hold a stock that provides the flow of services and has a cost consistent with its over-all budget plan. Upgrading adjustments are assumed to arise, when, because of changing needs and ability to pay, families find themselves with less than this desired amount of housing. Our approach to measuring this demand is based on two assumptions. First, we assume that families do not adjust their housing stocks instantaneously to changing demands. Rather, a considerable amount of time may elapse before they do something, which means they are in a position of disequilibrium for some time prior to making an adjustment. Second, we assume these families have significantly less housing than those who are in equilibrium. Given these assumptions, it is our contention that a cross section demand function, calculated from data for equilibrium families, will provide the basis for measuring potential upgrading demand. Such a function would be used to calculate expected stock values for all families in a cross section sample, which would then be compared with the actual stock values reported in the data. A simple analysis of the residuals should enable us to identify the disequilibrium families since, according to our assumptions, they would appear as families who have a deficiency in housing. Measures of housing space and quality are used as the basic dimensions of demand. Our model then consists of two sets of demand equations calculated from data ' for families who appear most likely to be in equilibrium. Equilibrium is defined in terms of attitudinal, purchase plans, and mobility status information included in the data. Where the head is under 45, we assume equilibrium families are those who have no plans to buy 2 or to make major additions to their current housing and have been living in their current residence for five years or less.3 Where the head is 45 or older, equilibrium families are assumed to be those who have no plans to buy or to make major additions to their present housing.4 The model is examined in two ways. First, since its success hinges on the presence of measurable differences between the housing stocks of equilibrium and disequilibrium 5 families, we test for these differences. The equations or norms are used to calculate housing demands for disequilibrium families, which are then compared with the actual housing available to these families.6 If there are